Gambaran Tingkat Pengetahuan Masyarakat Tentang Fenomena Childfree, Pengetahuan Penggunaan Kontrasepsi Secara Sudut Pandang Islam - Fathnin, Fildza Huwaina; Purnowati, Lusi Dwi; Khasanah, Pathatun (Sultan Agung Islamic University of Semarang, 2024)
Background: Childfree is still seen as a taboo among society, the culture and teachings that adhere to consider the childfree trend as a bad thing, the childfree phenomenon cannot be separated from the use of contraception. This childfree phenomenon is certainly interesting to study in more depth using a normative approach to Islamic law. Therefore, this study will discuss how society views childfree and examine the use of contraception from an Islamic perspective. Methods: The method used is a cross sectional. Therefore, the data used consists of the identity of the respondent, the respondent's knowledge of the childfree phenomenon, and an empirical study was carried out as secondary data to explain the results of the primary data. Results: The level of public knowledge regarding the childfree phenomenon is 64% who have good knowledge. Meanwhile, the results of research regarding the level of knowledge of the use of contraceptives from an Islamic perspective is 60%. Conclusion: The level of public knowledge regarding the phenomenon of childfree and the use of contraception according to Islamic views is in the good category. There is no very significant relationship between characteristics and respondents' knowledge regarding childfree knowledge and knowledge of contraceptive use.